(untitled) (Libya Journal of Geographical Studies, 2024)
The study examined urban expansion in the Zarrouk Municipal Branch during the period (1973-2020), relying heavily on remote data sensing technology, the computer technology provided by the geographical information environment, to derive layers of urban blocs from land uses, which can be sought to track the size of development in The invested urban island. The study combined two methods of spatial statistical design, two methods to evaluate the pattern and trend of the urban distribution of the region, and a method of evaluating the urban expansion area in the future in more diverse locations. The results are still present in the age structure and the proportion of flowers from 3.3 km2 in the year 1973 to 44.3 km2 in the year 2020, The results of the spatial statistical analysis measures showed that the nature of the urban distribution in the region takes a clustered form in all periods of the study, and that the most longitudinal directions in which urban growth occurred are in the south-south-southwest and south-southeast directions. Through spatial suitability analysis, it was possible to produce a map that best illustrates Suitable locations for the urban development of the region.